Investigation of proton conductivity of inorganic-organic hybrid membranes based on boronic acid and tetrazole - Sinirlioglu, Deniz; Muftuoglu, Ali Ekrem; Bozkurt, Ayhan (SPRINGER, 2014)
In this study, proton conducting membranes based on 4-vinyl benzene boronic acid (VBBA) and 5-(methacrylamido) tetrazole (MTet) were synthesized, and their thermal, electrochemical and proton conducting properties were explored. 5-(methacrylamido) tetrazole (MTet) was copolymerized with 4-vinyl benzene boronic acid (VBBA) via conventional free radical copolymerization. The obtained copolymers, P(VBBA-co-MTet), were then doped with phosphoric acid (PA) to produce inorganic-organic hybrid proton conducting membranes. Structural analyses were carried out by Fourier Transform Infrared Spectroscopy (FTIR) and H-1-NMR (NuclearMagnetic Resonance). The composition of the copolymers was determined by elemental analysis. Thermogravimetric Analysis (TGA) confirmed that the samples were thermally stable up to approximately 170 degrees C. The surface morphology was characterized by Scanning Electron Microscopy (SEM). Cyclic voltammetry (CV) results demonstrated that the oxidative stability of the samples is 3 V. In the absence of humidity, P(VBBA-co-MTet)-2H(3)PO(4) (S3-2H(3)PO(4)) has a maximum proton conductivity of 0.021 Scm(-1) at 150 degrees C. This value was higher than those of previously reported acid doped P(VBBA-co-VIm) and P(VBBA-co-VTri) membranes. Formation of highly conductive, flexible and insoluble free standing films indicates that the matrix has a potential to be used in proton exchange membrane fuel cells (PEMFC).
Keywords: 5-(methacrylamido) tetrazole; 4-vinyl benzene boronic acid; Proton conductivity; Polymer electrolyte membrane; Fuel cell; POLYMER ELECTROLYTE MEMBRANES; VINYL PHOSPHONIC ACID; FUEL-CELLS; FUNCTIONAL COPOLYMERS; PVDF; 5-(METHACRYLAMIDO)TETRAZOLE; BLENDS; Polymer Science